2016
DOI: 10.1016/j.ijhydene.2016.02.058
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen as electron donor for copper removal in bioelectrochemical systems

Abstract: Hydrogen gas is an attractive alternative electron donor since it is produced in large quantities as a side product in the metallurgical industry. Aim of this study was to demonstrate that microbial anodic hydrogen oxidation on a non-catalyzed graphite electrode can be coupled with cathodic copper reduction in a BES to simultaneously recover copper and produce power. The strategy was first to grow an anodic biofilm on acetate, then replace the acetate with hydrogen as electron donor, and finally combine hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 34 publications
2
18
1
Order By: Relevance
“…This scenario would require the presence of autotrophic electroactive cultures where bicarbonate is the carbon source for the biomass. Ntagia et al (2016) showed that hydrogen gas was directly oxidized at a bioanode with no detectable organic compounds in the anolyte 88 , a finding that was also observed in this study at 0 mM bicarbonate. However, the current density generated in Ntagia et al could only be sustained for a limited period of time (two weeks) when no additional carbon source was added, showing that the activity of electroactive autotrophs was dependent on carbon availability.…”
Section: Effect Of Bicarbonate Addition On Bioanode Performancesupporting
confidence: 84%
See 1 more Smart Citation
“…This scenario would require the presence of autotrophic electroactive cultures where bicarbonate is the carbon source for the biomass. Ntagia et al (2016) showed that hydrogen gas was directly oxidized at a bioanode with no detectable organic compounds in the anolyte 88 , a finding that was also observed in this study at 0 mM bicarbonate. However, the current density generated in Ntagia et al could only be sustained for a limited period of time (two weeks) when no additional carbon source was added, showing that the activity of electroactive autotrophs was dependent on carbon availability.…”
Section: Effect Of Bicarbonate Addition On Bioanode Performancesupporting
confidence: 84%
“…However, these industries often produce hydrogen gas, that is considered a waste stream. Previous research showed that hydrogen gas can be used as alternative to acetate as an electron donor at the bioanode in BESs 88 . Hydrogen gas was oxidized directly by bacteria on a graphite anode, eliminating the need for an expensive catalyst, which would be needed for electrochemical oxidation of hydrogen gas.…”
Section: Introductionmentioning
confidence: 99%
“…For the third scenario hydrogen was used as the electron donor, as it is produced in many metal industry locations. The use of hydrogen as an interesting alternative electron donor for the recovery of copper in BESs has been previously described by Ntagia et al …”
Section: Methodsmentioning
confidence: 99%
“…As an alternative for acetate, electron donors present in mining waste streams, like for example tetrathionate, have been tested for their suitability as bioanodes. In remote mining locations when waste streams are not available in the vicinity of metal streams, hydrogen, which is produced on site, could be used as an electron donor . Also, (bio)ethanol could be transported to these locations as a cheap organic alternative to acetate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation